SEGMENTASI MORPHOLOGI UNTUK DETEKSI KANKER PAYUDARA PADA DIGITAL MAMMOGRAFI - Anwar, Khoerul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
Abstrack: Breast cancer is expressed as dread disease for women in the world. Citra mammography is the image that can be used as a tool to detect keberdaan disease. The existence of the disease indicated in the characteristics of the object kanker breast tumors which appear in the image of mammography. In peper was presented algorithm segmentation morphologi with the process of opening and closing for the detection of breast tumors that appear in the image of mammography. Results dipeoleh shows the process is able to detect the presence of cancer in both the gray scale image.Â Keywords : mammografi, morphologi, thresolding, opening, closing